INOVASI PRODUK OLAHAN IKAN BANDENG MENJADI SAMBAL HIJAU "D'KRIIZ" UNTUK PENINGKATAN NILAI TAMBAH LOKAl - Ach Iqbal Bhayundha; Aimar Huda; Gizzeo Ogjha Bimma Subekti; Muhammad Dhawy Alwansyah; Kaila Tirta Tri Meifa; Rachmah Tri Inayah (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study examines the innovation of milkfish (Chanos chanos) processed products into a green chili condiment known as Sambal Hijau Bandeng "D'KRIIZ", as an effort to increase the added value of local wisdom in Sidoarjo Regency. Sidoarjo produces 35,271,900 kg of milkfish annually, yet UMKM-level processing remains limited to conventional products. The research objectives were to: (1) formulate and analyse a marketing strategy and determine strategic priorities; (2) assess the financial feasibility of the business; and (3) identify marketing progress and challenges. Data were collected through direct observation and transaction records from four production batches (April–May 2025) and supplemented by expert judgment for AHP analysis. Three analytical approaches were employed: the 4P marketing mix (product, price, place, promotion) combined with a Business Model Canvas; the Analytical Hierarchy Process (AHP) to rank strategic priorities; and financial feasibility indicators including HPP, R/C Ratio, NPV, Payback Period, ROI, Net B/C Ratio, and BEP. Results show that promotion received the highest AHP criterion weight (0.591), and the bundling package strategy ranked first among alternatives (0.618). Financially, the business achieved an R/C Ratio of 1.53, NPV of Rp218,116.13 (discount rate 15%), ROI of 41%, and a Payback Period of 0.71 months, confirming its economic viability. The main challenges include milkfish price fluctuations and limited production capacity, indicating the need for market expansion and production scale-up.